Zastosowanie modelu paleodemograficznego do rekonstrukcji historycznego procesu etnogenezy Słowian - Piontek, Janusz (Acta Universitatis Lodziensis. Folia Archaeologica, 1992)
The aim of the studies was to define the role of the two significant factors (natural selection and migration) in forming processes of adaptation and migration in the ethnogenesis of the Slavs. Two methodical approaches have been used: 1) a demographic model was constructed which could be applied for the analysis of migration process and the distribution of Slavonic groups, 2) simulating investigations were conducted which enabled to estimate the numbers and density of the population in various phases of the process of changes. As a measure for the adaptation level of population to the environmental conditions two palaeo-demographic measures were accepted: e°0 and the quotient of potential reproduction Rpot. It has been observed that the direction of migration of Slav groups was related to the ecological character of the occupied niche and colonized regions. The intensity of migration was dependant upon the level of differentiation of „the adoptive landscape” in the colonized region. Main factors, initiating migration processes were socio-cultural factors, enabling to migrate from „adaptive valleys” to the regions of better ecological characteristics, from the point of view of the economy of the early Slavs.